Using Culturally Sensitive Methodologies When Researching Diverse Cultures - Eboni J. Baugh; Lisa Guion (The Evaluation Center at Western Michigan University, 2006)
This article introduces additional information in the ongoing conversation about using culturally sensitive research methods with diverse research populations. Research, including evaluation research, examining ethnic minorities, international, tribal members, and individuals within diverse cultures should be performed within a context of cultural understanding. Several methodological examples will be presented, expanding the discussion of contemporary research with diverse cultures.